2015
DOI: 10.1002/pssa.201431700
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of III‐nitride laser diodes in solid‐state lighting

Abstract: III‐nitride laser diodes (LDs) are an interesting light source for solid‐state lighting (SSL). Modelling of LDs is performed to reveal the potential advantages over traditionally used light‐emitting diodes (LEDs). The first, and most notable, advantage is LDs have higher efficiency at higher currents when compared to LEDs. This is because Auger recombination that causes efficiency droop can no longer grow after laser threshold. Second, the same phosphor‐converted methods used with LEDs can also be used with LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…10 Additionally, the ability to fabricate single mode VCSELs is not only a benefit for data transmission but also makes VCSELs highly sensitive devices for atomic clocks. [11][12][13][14][15] Finally, because VCSELs have emission normal to the substrate, they can be fabricated into high density 2D arrays, making III-nitride VCSELs ideal for visible and UV-A applications requiring high power density emission, including pico-projectors, 16 micro-displays, [17][18][19][20] backlighting for small electronics, 21 laser based lighting, [22][23][24] and bio-sensing. 25 In the arsenides, high power VCSEL arrays are now being manufactured to yield 9.6 kW emission for rapid industrial heating, proving the potential for these low power devices to yield high power arrays.…”
mentioning
confidence: 99%
“…10 Additionally, the ability to fabricate single mode VCSELs is not only a benefit for data transmission but also makes VCSELs highly sensitive devices for atomic clocks. [11][12][13][14][15] Finally, because VCSELs have emission normal to the substrate, they can be fabricated into high density 2D arrays, making III-nitride VCSELs ideal for visible and UV-A applications requiring high power density emission, including pico-projectors, 16 micro-displays, [17][18][19][20] backlighting for small electronics, 21 laser based lighting, [22][23][24] and bio-sensing. 25 In the arsenides, high power VCSEL arrays are now being manufactured to yield 9.6 kW emission for rapid industrial heating, proving the potential for these low power devices to yield high power arrays.…”
mentioning
confidence: 99%
“…If blue-emitting lasers would be used instead of the LEDs, a high-power conversion efficiency could be achieved at much higher current densities, and the much higher optical output power generated by a single device would correspond to a smaller area to achieve the same lumens, resulting potentially in a lower cost for laser-based lighting systems. [11][12] A VCSEL offers a more directional, circular-symmetric beam, which could lead to new and more compact luminaires at a low cost. In addition, the individually addressable elements in a two-dimensional VCSEL array would enable tailor-made, dynamic emission patterns for smart lighting systems.…”
Section: Introductionmentioning
confidence: 99%
“…OCIS codes: (060.2605) Free-space optical communication; (140.7300) Visible lasers; (230.3670) Light-emitting diodes; (230.5590) Quantum-well, -wire and -dot devices; (250.0250) Optoelectronics; (250.5960) Semiconductor lasers.The past decade witnessed the rapid development of III-nitride light-emitting diodes (LEDs) [1,2], superluminescent diodes (SLDs) [3,4], and laser diodes (LDs) [5,6], for solid-state lighting (SSL), visible-light communication (VLC), optical storage, and internet-of-things (IoT) [7,8]. InGaN/GaN quantum well (QW)-based LEDs have been established as the fundamental component for SSL applications while recent studies suggested that the GaN-based LDs, which is free from efficiency droop, may outperform LEDs as a viable high-power light source [9,10]. Meanwhile, there are increasing potentials in using such emitters in visible-light based optical communication systems for indoor and outdoor applications as data-rate demands are exponentially growing in the near future [8,11,12].…”
mentioning
confidence: 99%